Factors Influencing the Intention of Perinatal Nurses to Adopt the Baby-Friendly Hospital Initiative in Southeastern Quebec, Canada: Implications for Practice - Guylaine Chabot; Marie Lacombe (Nursing Research and Practice)
Nurses play a major role in promoting the baby-friendly hospital initiative (BFHI), yet the adoption of this initiative by nurses remains a challenge in many countries, despite evidences of its positive impacts on breastfeeding outcomes. The aim of this study was to identify the factors influencing perinatal nurses to adopt the BFHI in their practice. Methods. A sample of 159 perinatal nurses from six hospital-based maternity centers completed a survey based on the theory of planned behavior. Hierarchical multiple linear regression analyses were performed to assess the relationship between key independent variables and nurses’ intention to adopt the BFHI in their practice. A discriminant analysis of nurses’ beliefs helped identify the targets of actions to foster the adoption the BFHI among nurses. Results. The participants are mainly influenced by factors pertaining to their perceived capacity to overcome the strict criteria of the BFHI, the mothers’ approval of a nursing practice based on the BFHI, and the antenatal preparation of the mothers. Conclusions. This study provides theory-based evidence for the development of effective interventions aimed at promoting the adoption of the BFHI in nurses’ practice.